Structure-based virtual screening of natural products as potential stearoyl-coenzyme a desaturase 1 (SCD1) inhibitors. (June 2020) - Huang, Yuzhou; Wang, Hanxun; Wang, Huibin; Wen, Rui; Geng, Xiaohui; Huang, Tianci; Shi, Jiyue; Wang, Xiujun; Wang, Jian
Graphical abstract: Highlights: Crucial protein-ligand interactions of SCD1 receptor antagonists were elucidated. TCMNP, ACDNP and IBSNP databases were screened for SCD1 receptor antagonists. MD simulation, binding free energy calculation and ADMET prediction were applied to evaluate the virtual screening hits. Abstract: Stearyl coenzyme A desaturase enzyme 1 (SCD1) is a key enzyme that catalyzes the conversion of saturated fatty acids (SFA) into monounsaturated fatty acids (MUFA) and plays a vital role in lipid metabolism of tumor cells. SCD1 is overexpressed in a variety of malignant tumors, and its related inhibitors showed significant anti-tumor activity in vitro and in vivo experiments, which is a new target for tumor therapy. The focus of this study is to identify novel SCD1 inhibitors from natural products through computer simulations. First, 176, 602 compounds from natural product databases were virtually screened. By molecular dynamics (MD) simulations, the ligand-protein interactions of 5 compounds with high docking manifestation were analyzed accurately. Then, MM-GBSA and MM-PBMA methods were used to verify the results. Finally, ADMET prediction was performed for the 5 compounds. As a result, two natural products with potential inhibition towards SCD1 were identified, which had the excellent docking manifestation, binding mode within SCD1 pocket and stability during molecular dynamics simulation. This study provides a meaningful model for the development and optimization of new inhibitors and anti-tumor drugs targeting SCD1.